2020
DOI: 10.1093/gji/ggaa262
|View full text |Cite
|
Sign up to set email alerts
|

3-D thermochemical structure of lithospheric mantle beneath the Iranian plateau and surrounding areas from geophysical–petrological modelling

Abstract: SUMMARY While the crustal structure across the Iranian plateau is fairly well constrained from controlled source and passive seismic data, the lithospheric mantle structure remains relatively poorly known, in particular in terms of lithology. Geodynamics rely on a robust image of the present-day thermochemical structure interpretations of the area. In this study, the 3-D crustal and upper mantle structure of the Iranian plateau is investigated, for the first time, through integrated geophysical–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…The crustal thickness in central Iran is approximately 45 km (Mousavi and Ebbing, 2018). In more recent studies, Mousavi and Fullea (2020) suggested a Moho relief using an integrated geophysical-petrological modeling approach.…”
Section: Previous Studies On the Zagros Sedimentary Cover And Mohomentioning
confidence: 99%
See 1 more Smart Citation
“…The crustal thickness in central Iran is approximately 45 km (Mousavi and Ebbing, 2018). In more recent studies, Mousavi and Fullea (2020) suggested a Moho relief using an integrated geophysical-petrological modeling approach.…”
Section: Previous Studies On the Zagros Sedimentary Cover And Mohomentioning
confidence: 99%
“…In this respect, we can refer to several published papers such as, Werner, 1953;Bott, 1960;Cordell, et al, 1968;Oldenberg, 1974;Parker, 1972;Reid, et al, 1990;Salem, et al, 2007;Martins, et al, 2011, Fedi, et al, 2012Sun, et al, 2015;Feng, et al, 2018;Florio, 2020, Schmidt et al, 2010and Sampietro, 2016 The depth of the Moho beneath the Iranian plateau has been investigated by several researchers through gravity modeling, (Dehghani and Makris, 1983;Snyder and Barazangi, 1986, Dehghan et al, 2021, Ebadi et al, 2019, Heydarizadeh Shali et al, 2020, Eshagh, 2014Ardestani and Mousavi, 2022). A combined gravity and magnetic modeling (Mousavi and Ebbing, 2018), seismic (Tatar, 2001;Javan-Doloei, 2002, Paul et al, 2006, Motaghi et al, 2015, integrated thermal modeling , Motavalli et al, 2011 and integrated geophysical-petrological modeling (Mousavi and Fullea, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Mousavi and Fullea [ 32 ] investigated the 3-D crustal structure of the Iranian plateau by integrated geophysical–petrological modeling combining elevation, gravity, and gravity gradient fields, seismic and petrological data. They estimated the maximum Moho depth equal to 65 km beneath the Zagros Mountain, while the thinnest crust was reported for the Oman sea and the central part of Iran [ 33 ].…”
Section: Introductionmentioning
confidence: 99%